Favorite Places of Indonesian Young Adults - Finta Lissimia (Department of Architecture Universitas Muhammadiyah Jakarta, 2018)
Study on favorite places reflects people’s preference for particular place. It may result in most likeable type of place and even the driving factors. Favorite place study can become the base for further research about preference. This type of study is very beneficial for spatial planning to find out what kind of setting will be successful. The purpose was to find out favorite place of young adult, specifically Indonesian people. Respondents in this study are restricted to 25-40 years old to produce strong result. In order to achieve this purpose, respondents will be asked about their favorite place. Data collected will be analyzed using distribution. There are 347 answers that can be analyzed further. Result show that favorite place of Indonesian young adults mostly are restaurants and beaches. It may have to do with lifestyle and geography of the area.